Innovation Opportunity, Social Media Utilization, and Customer Orientation: Empirical Study From The West Part of Java Land - Cipta Canggih Perdana; Fulgentius Danardana Murwani; David Sukardi Kodrat (Vifada Management and Social Sciences, 2026)
Purpose: This study investigates the impact of social media utilization on innovation opportunities, mediated by customer orientation, in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, focusing on information technology-based sectors in Banten, DKI Jakarta, and West Java. Research Design and Methodology: Using a purposive sampling technique and Partial Least Squares Structural Equation Modeling (PLS-SEM) for parameter estimation Findings and Discussion: The study finds that effective social media usage positively influences both innovation opportunities and customer orientation, which in turn impacts innovation opportunities. Moreover, customer orientation mediates the relationship between social media utilization and innovation opportunity. Data from 228 MSMEs confirm the validity and reliability of the tested variables. Implications: The study underscores that technology-based MSMEs should prioritize social media to enhance innovation and gather real-time customer data for market insights. With a strong customer orientation and effective social media capabilities, MSMEs can convert information into valuable insights to drive high-value-added product and service development, bolstering competitiveness. While highlighting managerial implications, the study acknowledges limitations in its regional scope and variables and recommends further research to explore the impact of social media capabilities on innovation.